Aminoaciduria in the prediction of ifosfamide-induced tubulopathy after childhood cancer: a feasibility study. Issue 1 (December 2016) - Morgan, Jessica; McKeever, Karl; Tyerman, Kay; Henderson, Michael; Picton, Susan; Phillips, Robert
Abstract Background Ifosfamide, an alkylating agent used widely in the treatment of childhood malignancy, can cause many side effects including a proximal tubulopathy. Studies suggest that aminoaciduria is seen most commonly of all the biochemical abnormalities of ifosfamide-induced tubulopathy. A recent systematic review has found a paucity of data regarding the value of early markers indicating clinically significant tubulopathy. We undertook a pilot study to determine the feasibility of examining whether patients can be risk-stratified on the basis of aminoaciduria for the development of future significant ifosfamide-induced tubulopathy, to allow the evolution of appropriate follow-up strategies. We also aimed to define accrual rates, costs and clinical demands for a future larger study. Methods This observational study recruited 21 patients from the Leeds Paediatric Oncology service. The medical notes of each patient were reviewed for demographic and clinical data. Simultaneous samples of blood and urine were obtained. Results The investigations in the feasibility study were acceptable to patients and were minimally demanding on both clinical and laboratory staff. Financially, the cost per patient was minimal. This study was not powered to detect significant associations with TmP/GFR (ratio of renal tubular maximum reabsorption rate of phosphate to glomerular filtration rate), growth and electrolyte supplementation. However, all patients with minimal aminoaciduria (≤2 elevated urinary amino acids) had normal TmP/GFR and no need for electrolyte supplementation. Conclusions This pilot study has shown that a larger study is feasible and may provide clinically useful data to change current practice. This should aim to establish whether the number of abnormal amino acids or the degree of abnormality is most significant in predicting clinically significant proximal tubulopathy. Trial registration NHS REC Leeds West Ref 10/H1307/22